Makna Media Massa Bagi Komunitas Sedulur Sikep Dukuh Kaliyoso Desa Karangrowo Undaan Kudus - Fitriyah, Anis (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
Sedulur sikep community are one of Javanese tribes who still continoue their ancestral tradition. They discard all of modernization including mass media, trading, politics, and trading. Therefore this article aims to reveal the meaning of mass media from Sedulur sikep perspective and how they response to the mass media existance. This research is a descriptive qualitative method. The results shows that the Sedulur Sikep community manifested the mass media in three attitudes; 1) rejecting the media, carried out by the older generation, 2) semi accepting the mass media with motivational needs and 3) receiving in full, in addition to taking Sedulur sikep in disseminating the information through the internet.